2012
DOI: 10.1039/c1nr11068c
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in vertically aligned, self-assembled peptidenanotube junctions

Abstract: The self-assembly propensity of peptides has been extensively utilized in recent years for the formation of supramolecular nanostructures. In particular, the self-assembly of peptides into fibrils and nanotubes makes them promising building blocks for electronic and electro-optic applications. However, the mechanisms of charge transfer in these wire-like structures, especially in ambient conditions, are not yet fully understood. We describe here a layer-by-layer deposition methodology of short self-assembled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…As implied by its name, the fibril formation inhibitor cyclic peptide, cyc [60][61][62][63][64][65][66][67][68][69][70] (Fig. 7c), has two contrasting faces, one hydrophobic and the other hydrophilic [98,102].…”
Section: Janus Cyclic Peptidementioning
confidence: 98%
See 3 more Smart Citations
“…As implied by its name, the fibril formation inhibitor cyclic peptide, cyc [60][61][62][63][64][65][66][67][68][69][70] (Fig. 7c), has two contrasting faces, one hydrophobic and the other hydrophilic [98,102].…”
Section: Janus Cyclic Peptidementioning
confidence: 98%
“…Atomic force microscopy (AFM), CD spectroscopy, and EM showed that no amyloid fibrils were formed upon aging of cyclo 17,21 ]Aβ (1-28) contained higher amounts of α-helical structures than Aβ28 and that the two ]Aβ (1-28), a cyclic derivative of a full-length Aβ [97]. (c) Ribbon and CPK representation of the Janus cyclic peptide cyc [60][61][62][63][64][65][66][67][68][69][70] showing the persistent intramolecular backbone hydrogen bonds in blue [98] Anti-amyloidogenic Heterocyclic Peptides peptides interacted to prevent the generation of Aβ amyloid. Moreover, a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay suggested that cyclo 17,21 -[Lys 17 ,Asp 21 ]Aβ(1-28) protected human glioblastoma/astrocytoma cells from Aβ28-induced toxicity.…”
Section: Conformational Restrictorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These assemblies have been exploited for applications of biosensing, drug delivery, molecular electronics, etc. [38][39][40][41][42][43][44][45] This paper describes the experimental steps needed in order to start the spontaneous self-assembly of homoaromatic peptides. In addition, it presents the process of peptide coassembly.…”
Section: Introductionmentioning
confidence: 99%